Physicochemical Properties of Soil and Water Along Haro River and Khanpur Dam, Haripur, Pakistan: Physicochemical Properties of Soil and Water Along Haro River and Khanpur Dam, Haripur, Pakistan - Jamal, Rehana; Ikram, Muhammad; Ahmad, Sajid Rasheed; Khan, Khalida (International Journal of Economic and Environmental Geology, 2018)
This study was conducted along the Haro River and Khanpur dam in southern Haripur Tehsil to evaluate the physio-chemical properties of soil and water to determine its agricultural suitability and to demonstrate the effectiveness of GIS techniques for this analysis. There were 42 samples (20 of soil and 22 of water) collected along the Haro River and Khanpur dam in autumn season after rain. ArcGIS 9.3 software and 3D Analyst extension were used to interpolate the collected samples. It was found that water pH was in the range of 6.94 to 8.11 while EC dsm-1 was from 0.19 to 0.41 which was within the normal range having no salinity and sodicity hazard. Water is fit for irrigation. Soil data showed that pH was in the range of 7.2 to 8.32 and EC dsm-1 in the range of 0.04 to 1.166, while soil texture was sandy clay loam to sand type. Whereas all the soil in study area was mostly calcareous. Organic matter was deficit in most of the soil samples. It was found that the remote sensing, GIS and GPS survey techniques were also very useful to identify and analyze the trends of soil and water parameters.